PHYSIOTHERAPY IN ELDERLY PERSONS WITH CEREBROVASCULAR ACCIDENT (AVC) SEQUELS - Gussi, Dhayara; Camilla Freitas Dos Santos, Estefhany; Neves Lopes, Maria (Health and Society, 2023)
The present work aims to report the importance of physiotherapy in the rehabilitation process in elderly people with sequelae of stroke, a disease that is responsible for many deaths and leaves many sequels. Physiotherapy after stroke should start as soon as possible, as the faster the patient is stimulated, the faster his recovery will be, with a view to improving the quality of life and recovering lost movements. It will be used for the recovery of various physiotherapeutic techniques such as electrothermal therapy, kinesiotherapy, hydrotherapy aimed at recovering strength and mobility in order to make the elderly more independent in their activities, helping to maintain mental health and returning to their routine. Physiotherapy can obtain several benefits depending also on the patient’s will, family support and the work of a multidisciplinary team composed of a doctor, nurse, physiotherapist, speech therapist, nutritionist and psychologist.